The effect of storage time of chopped oil palm fruit bunches on the palm oil quality - Ali, Fatin Syakirah; Shamsudin, Rosnah; Yunus, Robiah (Elsevier, 2014)
The bulkiness of the fresh fruit bunches (FFB) cause ineffectiveness of heat distribution into the inner layers of the fruits and simultaneously led to poor palm oil quality. Thus, this research was conducted to determine the effect of storage time of chopped FFB on the palm oil quality and stripping efficiency. The FFB was chopped using a fabricated chopper blade and stored for 30 min to 120 min. The results showed that the FFA, moisture content, DOBI and carotene content were ranged 1.19% -2.21 ± 0.394%, 0.175 - 0.411 ± 0.097%, 2.74 - 0.85 ± 0.746 and 430.402 - 326.081 ± 0.768 ppm respectively. The chopped FFB also had better stripping efficiency compared to unchopped FFB